Considerations on affectivity in teaching relations: Vygotsky’s contributions (Acta Scientiarum. Education, 2015)
The objective of this article is to present conclusions of a study about the affective matter from an inter-relational perspective with cognition, as a single unit – the human psychic life â€‘, which means to conceive that affection is present in and constitutive of any and every human action. This research is theoretically based on studies conducted by L.S. Vygotsky. We also made use of contributions by some of his commentators or interpreters that addressed this theme specifically. The text is part of the theoretical foundations of the doctoral thesis on this subject, in empirical context – a youth and adult education class.